Analisis Penentuan Harga Pokok Produksi Telur Asin dengan Menggunakan Metode Full Costing - Lestari, Lamsah; Awalia, Erly Nur; Sari, Novita (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2024)
The research aims to analyze the price determination of salted egg production using the full coasting method at UMKM. Data collection techniques use observation, interviews and documentation methods. The results of this research show that there are differences in calculating the cost of production using the UMKM method at CV. Keramat Telur Berkah with the full coasting method. The basic price for producing boiled salted eggs using Mrs. Emi's UMKM method was IDR. 3,220,- full coasting method IDR. 3,426,- difference IDR. 207,- Mrs. Emi's grilled salted egg IDR. 3,585,- full coasting method IDR. 3,847,- difference IDR. 262,- then for Mrs. Emi's baked salted eggs, the cost of production is IDR. 3,497,- full coasting method IDR. 3,731,- difference Rp. 234,-. Keywords: UMKM, Cost of Goods Production, Full Coasting Method